2020
DOI: 10.1371/journal.pone.0243893
|View full text |Cite
|
Sign up to set email alerts
|

Regular exposure to a Citrus-based sensory functional food ingredient alleviates the BOLD brain responses to acute pharmacological stress in a pig model of psychosocial chronic stress

Abstract: Psychosocial chronic stress is a critical risk factor for the development of mood disorders. However, little is known about the consequences of acute stress in the context of chronic stress, and about the related brain responses. In the present study we examined the physio-behavioural effects of a supplementation with a sensory functional food ingredient (FI) containing Citrus sinensis extract (D11399, Phodé, France) in a pig psychosocial chronic stress model. Female pigs underwent a 5- to 6-week stress protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 63 publications
(96 reference statements)
0
8
1
Order By: Relevance
“…Functional food ingredients derived from natural extracts are of growing interest in human and animal nutrition to optimize food intake and improve well-being through adaptation to potential stressors for example (1). Usually composed of aromatic substances (essential oils, aromatic herbs, spices, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional food ingredients derived from natural extracts are of growing interest in human and animal nutrition to optimize food intake and improve well-being through adaptation to potential stressors for example (1). Usually composed of aromatic substances (essential oils, aromatic herbs, spices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In previous preclinical studies in a pig model of chronic psychosocial stress characterized by social isolation, environment impoverishment and unpredictability (10), we have shown that functional food ingredients (FI) based on spice extracts (Curcuma longa L., Piper nigrum L., Capsicum annuum L., and Zingiber officinale L.) or Citrus sinensis could induce food preference and have possible anxiolytic properties, while modulating brain activity and plasticity in regions involved in pleasure, emotion regulation and cognition (1,11). Indeed, animals that had supplemented feed with a functional ingredient had a lower number of escape attempts within the openfield test arena and a lower latency to eat during the novelty-suppressed feeding test compared to the control group (11).…”
Section: Introductionmentioning
confidence: 99%
“…In support of that, Val-Laillet et al ( 17 ) demonstrated that feeding pigs a C. sinensis based CE feed additive had positive impacts on brain activation in the insular cortex, the amygdala, and the striatum (putamen and caudate), suggesting that the CE stimulated reward perception and anticipation in pigs. Finally, an imaging study in pigs treated with a C. sinensis based CE feed demonstrated that olfactory stimulation induced by this ingredient increases the activity of several brain regions associated with the regulation of cognitive and emotional processes ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to citrus extract (CE) essential oil, derived from Citrus sinensis ("sweet orange"), has been demonstrated to reduce anxiety in male Wistar rats (12) and reduce mean blood pressure, respiratory rate, and pulse rate in children during a stressful situation (13). Similarly, Menneson et al (14) demonstrated that pigs that exposed to CE had a lesser stress response when injected with a substance to induce stress than pigs not exposed to CE. Perhaps most compellingly, Lehrner et al (15) observed that, in a study of men and women, diffusing C. sinensis essential oil into a dental office waiting room reduced self-reporting of anxiety and increased reporting of factors associated with positive mood (n = 50 subjects) compared with a control (no scent; n = 51 subjects).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we chose to use the minipig model because this species presents many similarities with the human in terms of organ size and proportions, notably gastrointestinal tract anatomy, morphology, and physiology, besides having a quite large gyrencephalic brain better suited for brain functional imaging [10,11]. Our INRAE research group gained renowned expertise on the minipig model for nutrition and neuroscience research and have implemented various in vivo brain imaging strategies to explore in pigs the brain activity and metabolism in response to olfactogustatory and other kinds of relevant stimulations [12][13][14] but also in the context of diet-induced obesity [11,15]. In a recent review paper, we presented the obesity animal models for acupuncture and related therapy research studies [1].…”
Section: Introductionmentioning
confidence: 99%